Analysis Information System Primary Care BPJS Health at Puskesmas in Mukomuko Regency Using Technology Acceptance Model (TAM) - Suci Anggun Dewi Lestari; Suzi Oktavia Kunang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
BPJS is an agency that administers the National Health Insurance (JKN). BPJS Health developed a BPJS Primary Care (P-Care) that is accessed using the internet that integrates data into the BPJS server covering the patient registration process, diagnosis, therapy to laboratory services. So that it can make it easier for the medical team to provide treatment. The application of the Pcare BPJS information system in Mukomuko Regency has been used since 2015 and is always experiencing system development and updates. This information system cannot be used for the public, meaning that it is used only by health facilities that have officially registered with the BPJS who have been given access rights and passwords to access them. This study aims to analyze operator acceptance of the BPJS P-Care information system at the Mukomuko District Health Center using the Technology Acceptance Model (TAM) method which consists of 5 variables, namely Perceived Ease of Use (perceived ease of use), Perceived Usefulness (perceived usefulness), Attitude Towards use (attitude towards use), Behavior Intention to Use (interest in usage behavior) and Actual Usage (actual use). The results of this study are the identification of the acceptance of 16 puskesmas operators in Mukomuko Regency to the BPJS Health P-Care information system which will later become input for the BPJS in improving the system they have created.